Correlation between the kinematic parameters situation the free kick of elite players - Aziz, D.; Bylbyl, S. (American Journal of Sports Science, 2019)
This research is aimed at reviewing the correlation of seven situational kinematics parameters of the free kick of the elite soccer players (Cristiano Ronaldo): Angle of approach, Distance of free kick to the middle of the goal, Distance of the ball approach, Number of steps of ball approach, Length of the last step, Distance between the ball and the support leg, Angel inclination of the support leg. We used the cinematographical method through Kinovea- and Photo Suite 4, to 30 free kick videos -You Tube. Measurements of kinematics variables are measured directly in some frames to stages of movement, and after basic statistical analysis and Pearson's Correlation Coefficient (r). With six first variables we have analyzed the Approach phase where correlations significant positive relationships expressed variables Number of steps of ball approach - Ns with three other variables: Distance of the ball approach - Da, r = 0.431 (p =.020) and The length of the last step - Ls, r = 0.397 (p =.033) and Angle inclination of the support leg - phi, r = 0.443 (p = 0.018). as well as the variable Length of the last step -Ls, which also has significant positive relations correlations with the variable Distance of the ball approach, running start -Da, r = 0.745 (p =.000). Relationships between the off side and the free location and the angle of approach, the kicking in the same angle of the same side of approach have a value of about 30 degrees, and if it falls to the opposite angle of the opposite side, the angle of access has a value of about 50 deg.